(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nature has bestowed the beautiful capacity to procreate a life within woman and every woman cherishes the experience of motherhood. But, unfortunately some women due to certain physiological conditions could not give birth to their own off-spring, sometime infertility among married couples is a major problem affecting not only their marital life but also their social life and it is generally known as a social stigma in India as in Indian society the family structure has a very stable structural format with a set of parents with a strong desire for children and particularly for son to carry forth the lineage or Vansh. With the tremendous advances in the field of medicine, the infertility would now be able to be treated utilizing the new medical advances all in all called as Assisted Reproductive Technology (ART, for example, in vitro preparation (IVF) or Intra Cytoplasmic Sperm Injection (ICSI), and so on. Surrogacy can help one couple to have child but they least take care about the health of surrogate mother and its effect on the growth of child because they didn’t knew the whole medical procedure and its technical issues. Moreover, the emotional and other health factors remain unaddressed even after sentencing the judgments by the courts. So this Article is an initiative to address the problems of health and other issues of surrogate mother and child too.